2016
DOI: 10.2106/jbjs.15.00344
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Assessment of the Anterolateral Ligament of the Knee

Abstract: Since the anterolateral ligament engages only during pathologic ranges of tibial translation, there is a limited need for anatomical reconstruction of the anterolateral ligament in a well-functioning ACL-reconstructed knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(48 citation statements)
references
References 28 publications
3
44
0
1
Order By: Relevance
“…These data confirm the hypothesis of Thein et al [20]. They described the ALL as the "secondary stabilizer" to the ACL.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data confirm the hypothesis of Thein et al [20]. They described the ALL as the "secondary stabilizer" to the ACL.…”
Section: Discussionsupporting
confidence: 91%
“…There are cadaveric studies describing the role of this structure for the anterior-posterior and rotational stability of the knee [13,19,20]. The main role of the ALL is to prevent the Research Paper Komzák, Hart, Paša, Šmíd, Náhlík, et al After putting the patient under anesthesia, the femur was fixed using a standard metal holder.…”
Section: Introductionmentioning
confidence: 99%
“…Sonnery-Cottet et al [51] and Monaco et al [34], both utilizing navigation, demonstrated increased internal rotation laxity during a dynamic pivot shift test following an ACL/ITB deficient and ACL/ALL deficient setting respectively. published their findings in a serial sectioning study showing that the ALL only engaged in load sharing beyond the physiological limits of the ACL [57]. As such they concluded that the ALL was a secondary stabilizer to anterolateral translation only after loss of the ACL, rather than a co-stabilizer.…”
Section: Biomechanics Of the Anterolateral Structuresmentioning
confidence: 97%
“…Unfortunately, this experiment was performed after the ITB had been removed, and so the percentage contributions would have been over-stated, because the ITB has since been shown to be the primary restraint (see below). Thein et al [61] found that the ALL had resisted <10 N force during a tibial anterior translation test, and <17 N during the simulated pivot-shift test; thus, they concluded that the ALL could only be considered a secondary restraint.…”
Section: Anterior–posterior and Internal–external Rotation Laxity Of mentioning
confidence: 99%